A Study on Working Conditions of Unskilled Migrant Labourers in Kerala with Special Reference to Ernakulam District - Saviour F
The present paper throws light upon the working environment of the migrant labourers in the state of Kerala. It focusses on the unskilled labourers who work in the unhealthy working conditions of the industrial sector. In spite of their vital role in the economic growth of the state, they are made to work for more than the stipulated time, not even paid for the overtime work. These unskilled labourers and their families face health issues due to the hazardous work and improper medical care. It is a fact that they are employed as temporary workers with neither proper wages nor any other benefits. They are not even added in any of the official records of the city. Even though they face difficulty in the work place, they prefer to stay in the state itself, because of work opportunities. Hence there is a dire need to preserve the interests of these unskilled migrant labourers to protect the social and economic well- being of the state as a whole.